AGE AND COMPRESSIVE STRENGTH OF CONCRETE FROM VARIOUS BRANDS OF PORTLAND COMPOSITE CEMENT (PCC) - I Wayan Intara; I Ketut Sutapa (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
. Recently it is provided in the construction market several types of cement such as OPC (Ordinary Portland Cement), White Cement and most recently is PCC (Portland Composite Cement). The composition of PCC cement’s raw materials is Clinker, gypsum and additive materials. Additive materials used are limestone, fly ash and Trass. Unlike OPC type which does not use Fly Ash and Trass additives, in PCC it is used additives like Fly Ash and Trass where there is SiO2 compound that can increase the compressive strength. The research was carried out at the Laboratory of Civil Engineering Department of the Bali State Polytechnic using a cylindrical test object with size 15x30 cm of 20 pieces for each concrete age with a compressive strength of 25 MPa plan, tested at the age of 3, 7, 14, 21, 28, 56, and 90 days following PBI'71. The concrete strength of the concrete characteristics of the plan was achieved at the age of 56 days, with the value of the compressive characteristic of the plan reached at age 56 days with consecutive values ​​of 25.82, 27.67, 26.80, 31.20 MPa and 28.81 MPa for Tonasa, Holcim, Bosowa, Merah Putih, and Tiga Roda cements. This value is greater than the value of compressive strength targeted based on the calculation of job mix design, in which it is 25 MPa. Conversion of Age and Compressive Strength Characteristics for the 5 (five) brands of PCC cement.